Virtual Reality communication training tool for optimizing placebo- and minimizing nocebo-effects: Presenter(s): Liesbeth van Vliet, Health, Medical and Neuropsychology Unit, Institute of Psychology, Leiden University, Netherlands. (April 2023) - Westendorp, Janine; Peerdeman, Kaya J.; Meeuwis, Stefanie H.; olde Hartman, Tim C.; Sanders, Ariëtte R.J.; Godfried, Marc B.; Thiel, Bram; Evers, Andrea M.
Abstract : Background: Among experts and clinicians in the field of placebo research, there is consensus that healthcare providers should preferably be trained to optimize placebo- and minimize nocebo-effects while treating their patients. However, no widely available training currently exists to teach them how to do this. We are developing an innovative virtual training tool based on the most recent scientific insights and expert consensus, that has been investigated systematically by Delphi methodology during two expert meetings. Methods: The aim of the training is threefold: 1) to familiarize healthcare professionals with state-of-the art theoretical knowledge on placebo- and nocebo-effects, 2) to raise awareness of placebo- and nocebo-effects in everyday clinical practice, 3) to train skills to optimize placebo-effects and minimize nocebo-effects. During the developmental process there is structural collaboration with communication experts and clinicians. To ensure that the virtual training tool is successful and user friendly, usability and feasibility assessments are performed by experts in the field of placebo research and naïve end-users. Findings: The training is currently under development and will include both theoretical Background: and hands-on practice, including communication with simulated virtual patients. The training uses advanced virtual reality elements, allowing healthcare providers to interact with simulated patients. Results: of the usability and feasibility assessments are currently being collected and analyzed. Discussion: This training offers a pioneer application of a field of research that has been shown to have great potential to improve health outcomes. The tool is unique in its broad applicability, since it can be used by physicians of all disciplines as well as other healthcare providers. Healthcare providers will be able to access the tool on a virtual platform from their own work space. Future research projects will investigate the effects of the virtual training tool in healthcare professionals on treatment outcomes in patients.